EFFECT OF COMBINED BOBATH AND BALANCE EXERCISE THERAPY ON PHYSICAL MOBILITY IMPROVEMENT IN STROKE PATIENTS: A CASE STUDY - Sulistiyawati, Sri; Septianingrum , Yurike; Soleha, Umdatus; Wijayanti, Lono (Library Unit collaborates with the Institute for Research and Community Service, College of Health Sciences Husada Jombang, 2025)
Background: Stroke emerged as a serious global health problem, ranking as the leading cause of disability and the second leading cause of death worldwide. The most common impact of stroke was impaired physical mobility, especially with damage to the brain's motor centers or nerve pathways controlling body movements. In stroke patients, this disorder could appear directly after an acute attack and persist into the rehabilitation phase if not treated properly. One intervention to address physical mobility disorders in stroke patients was the application of a combination of Bobath therapy and balance exercises to accelerate motor function recovery, prevent immobilization complications, and increase patient independence. Objectives: This case study aims to analyze the effectiveness of the application of the combination of Bobath therapy and Balance exercise on physical mobility disorders in stroke patients. Methods: This study is a case study of a description of one stroke patient in Mrs. S in the Arjuna Room of Bhakti Dharma Husada Hospital Surabaya by using a descriptive nursing process with an approach to describe in depth the application of the intervention to the patient. Results: The implementation of a nursing intervention in the form of a combination of Bobath therapy and balance exercise who experienced physical mobility impairment due to non-hemorrhagic stroke for six days showed positive results. Conclusion: The increase in muscle strength can be seen from the patient's ability to maintain posture, transition from lying down to sitting to standing, and show better stability during balance exercises.